Aplikasi Importance Performance Analysis (IPA) Dalam Menilai Kualitas Pelayanan Jasa Pendidikan Pada Perguruan Tinggi Swasta Di Wilayah IVB APTISI Jawa Barat - Saepudin Saepudin; Welly Surjono; Tevi Leviany (Jurnal Ekonomi Manajemen Perbankan, 2020)
Quality higher education is expected to produce quality human resources, this can be seen with the existence of Higher Education Accreditation. The purpose of this study is to determine the results of the assessment using the IPA method of the variable quality of education services at PTS in the IVB region APTISI West Java (Purwakarta and Subang ) as well as mapping the scores of assessment results using IPA into a Cartesian diagram. The method used is descriptive (survey) method. The population in this study were private university students in high schools in the IVB region of APTISI West Java (Purwakarta and Subang). Sampling was carried out proportionally with the Slovin formula. Based on the testing, PTS IKM in total (average) was 0.70, included in the good category. The results of testing the hypothesis that the performance of each service quality variable based on the results of respondents' assessment scores of 70.20%. This condition is still below 100% which means it is not satisfactorily maximally because there is still a gap of 27.80%, then the hypothesis which states that the determinant variable of the quality of education services will have a total effect on PTS student satisfaction has not been proven significantly. Physical evidence, reliability, responsiveness, and empathy are in quadrant A. This means that the performance of these variables is lower than the desire of PTS students in the IVB region of APTISI West Java (Purwakarta and Subang). Guarantee variable is in quadrant D. This means that the performance of the variable is at a high level, however the student's desire for the variable's performance is only low.